The semillero as a pedagogical strategy to promote research in SENA apprentices. Case Study: CDTCI, Quindío - Castaño Aguirre, Carlos Alberto
This article reflects on the research incubators o semilleros as a pedagogical and training strategy addressed in the Center for the Technological Development of Construction and Industry, SENA, aligned with the pedagogical model of training by projects and its integrality. From the experience of instructors and apprentices linked to semilleros, the processes and achievements of the research training and its contribution to the missionary process of SENA are exposed, as well as the contribution to the problems, in real contexts, worked by the training center.